EUFEMISME DAN DISFEMISME PADA MEDIA BERITA DARING REPUBLIKA: PERKEMBANGAN KASUS SETYA NOVANTO EDISI JANUARI 2018 - Heryana, Nanang (Universitas Tanjungpura, 2019)
AbstractThis research aims to identify, describe, and analyze the use of euphemism and dysphemism from the forming process, meaning, and function of Republika online media related to the Development of Setya Novanto Case in January 2018 edition.Â Method used is descriptive with qualitative approach. Data source is news issued by Republika online regarding Setya Novanto Case Development in January 2018 edition many as 15 news issues. Research data is the use of euphemism and dysphemism including word, phrase, clause, and sentence. Data collecting technique used is documentation and tool of data collecting is news capture. Data analysis method used are identity and distributional method. The meaning of euphemism and dysphemism including collocative meaning and connotative meaning either in form of word, phrase, or clause. Euphemism can function as a protective tool, smoothing utterance, provocation, encouragement, fraud cover, and diplomacy. Dysphemism can function as a negative image of someone or something, showing low value thing, exaggerate something, and showing disrespect.Â Â Key Words: Euphism, Dyshemism, Republika Online, Setya Novanto Case